Early B-cell Factor1 (Ebf1) promotes early osteoblast differentiation but suppresses osteoblast function - Nieminen-Pihala Vappu; Tarkkonen Kati; Laine Julius; Rummukainen Petri; Saastamoinen Lauri; Nagano Kenichi; Baron Roland; Kiviranta Riku (Elsevier Inc., 2022)
Early B cell factor 1 (Ebf1) is a transcription factor that regulates B cell, neuronal cell and adipocyte differentiation. We and others have shown that Ebf1 is expressed in osteoblasts and that global deletion of Ebf1 results in increased bone formation in vivo. However, as Ebf1 is expressed in multiple tissues and cell types, it has remained unclear, which of the phenotypic changes in bone are derived from bone cells. The aim of this study was to determine the cell-autonomous and differentiation stage-specific roles of Ebf1 in osteoblasts.
In vitro, haploinsufficient Ebf1+/− calvarial cells showed impaired osteoblastic differentiation indicated by lower alkaline phosphatase (ALP) activity and reduced mRNA expression of osteoblastic genes, while overexpression of Ebf1 in wild type mouse calvarial cells led to enhanced osteoblast differentiation with increased expression of Osterix (Osx). We identified a putative Ebf1 binding site in the Osterix promoter by ChIP assay in MC3T3-E1 osteoblasts and showed that Ebf1 was able to activate Osx-luc reporter construct that included this Ebf1 binding site, suggesting that Ebf1 indeed regulates osteoblast differentiation by inducing Osterix expression.
To reconcile our previous data and that of others with our novel findings, we hypothesized that Ebf1 could have a dual role in osteoblast differentiation promoting early but inhibiting late stages of differentiation and osteoblast function. To test this hypothesis in vivo, we generated conditional Ebf1 knockout mice, in which Ebf1 deletion was targeted to early or late osteoblasts by crossing Ebf1fl/fl mice with Osx- or Osteocalcin (hOC)-Cre mouse lines, respectively. Deletion of Ebf1 in early Ebf1Osx−/− osteoblasts resulted in significantly increased bone volume and trabecular number at 12 weeks by μCT analysis, while Ebf1hOC−/− mice did not have a bone phenotype.
To conclude, our data demonstrate that Ebf1 promotes early osteoblast differentiation by regulating Osterix expression. However, Ebf1 inhibits bone accrual in the Osterix expressing osteoblasts in vivo but it is redundant in the maintenance of mature osteoblast function.